ANALISIS IMPLEMENTASI LITERASI NUMERASI DI SEKOLAH DASAR NEGERI 02 KARANGROTO - Nugraheni, Setyo Wuri Kartika (Universitas Islam Sultan Agung, 2024)
Numerical Literacy is one of the derivative branches of mathematical literacy, which is a combination of arithmetic, numeracy relations, and arithmetic operations which are important skills and are much needed to improve the quality of education in Indonesia. The purpose of this research is to find out the implementation from the point of view of aspects of numeracy literacy indicators and to be useful as a reference for other institutions in implementing numeracy literacy in elementary schools. This type of research uses a qualitative description method with observation, questionnaires, and interviews. the result of this study is that the implementation of numeracy literacy at SD Negeri 02 Karangroto has been going well. Evidenced by the student questionnaire in filling out the indicators of numeracy literacy, the majority of which are already known by students. Therefore, the study found can become data for SD Negeri 2 Karangroto in developing numeracy literacy learning on indicators that are still not in good category so that they can achieve the expected goals.